2018
DOI: 10.1093/brain/awy039
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic group 3 medulloblastoma is driven by PRUNE1 targeting NME1–TGF-β–OTX2–SNAIL via PTEN inhibition

Abstract: Genetic modifications during development of paediatric groups 3 and 4 medulloblastoma are responsible for their highly metastatic properties and poor patient survival rates. PRUNE1 is highly expressed in metastatic medulloblastoma group 3, which is characterized by TGF-β signalling activation, c-MYC amplification, and OTX2 expression. We describe the process of activation of the PRUNE1 signalling pathway that includes its binding to NME1, TGF-β activation, OTX2 upregulation, SNAIL (SNAI1) upregulation, and PTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 77 publications
1
59
0
1
Order By: Relevance
“…after reducing OTX2 level [22]. In the same work, it is also reported that OTX2 level is positively correlated with TGF-signaling activity.…”
Section: Biological Evaluation Of Dynamic Model Outputs ¾ Increased Umentioning
confidence: 66%
See 1 more Smart Citation
“…after reducing OTX2 level [22]. In the same work, it is also reported that OTX2 level is positively correlated with TGF-signaling activity.…”
Section: Biological Evaluation Of Dynamic Model Outputs ¾ Increased Umentioning
confidence: 66%
“…Even though the behaviors of subroutines that could activate MYC are not mentioned [22], we still investigate the simulated behaviors of those subroutines after OTX2 silencing in our study.…”
Section: Biological Evaluation Of Dynamic Model Outputs ¾ Decreased Umentioning
confidence: 99%
“…While activation of the TGFβ/Activin pathway has been described in SHH group, no data are currently available regarding its activation in Group 3. A recent report showed that Prune‐1 may activate the TGFβ pathway in Group 3 MB but the level of pathway activation in Group 3 was not investigated nor its functional relevance (Ferrucci et al , ). It has also been suggested that TGFβ ligands determine the promigratory potential of bFGF signaling in MB but this study was performed in non‐Group 3 cell lines and in atypical MB‐PDX (Santhana Kumar et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, this signaling pathway reduces MYC expression (Warner et al , ; Seoane et al , ), although it can be induced in human embryonic stem cells (Brown et al , ). Since OTX2 has been demonstrated to be a major Smad2/3 target gene in the nervous system (Jia et al , ), it has been proposed to be a Smad2/3 inducible gene in Group 3 MB (Ferrucci et al , ) and considered as part of this signaling pathway in MB (Northcott et al , ). We did not detect any consistent changes in MYC and OTX2 expression upon modulation of the Activin pathway, suggesting that this signaling pathway does not regulate these two genes in Group 3 tumors and promotes tumor growth through other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editors, Prune-1 is a member of the DHH (Asp-His-His) phosphoesterase protein superfamily involved in the regulation of cell proliferation and migration. [1][2][3] In humans, the gene Prune-1 is located in the 1q21.3 chromosomal region (epidermal differentiation complex) making it a good candidate for skin proliferation/differentiation and regulation. In a transgenic mouse model characterized by cutaneous hyper-proliferation, H-prune-1 has been associated with epidermal proliferation and keratinocyte differentiation, increased expression of pro-inflammatory cytokines and alteration of the skin barrier.…”
mentioning
confidence: 99%